Cretaceous seawater and hydrothermal fluid compositions recorded in abiogenic carbonates from the Troodos Ophiolite, Cyprus - Weinzierl, Christoph; Regelous, Marcel; Haase, Karsten; Bach, W.; Böhm, F.; Garbe-Schönberg, D.; Sun, Yadong; Joachimski, Michael; Krumm, Stefan (Chemical Geology, 2018)
Keywords: 87Sr/86Sr; Akaki; Carbonates; CO2; Alteration; Calcites; Hydrothermal fluid; Mg/Ca; Cretaceous; Fluid evolution; Seawater composition; Seawater; oxygen isotopes; Ophiolite; Troodos; Thermodynamic model; Sr/Ca; Seawater-rock reaction; δ44/40Ca

Evidence for melting of subducting carbonate-rich sediments in the western Aegean Arc - Wölki, Dominic; Haase, Karsten; Schönhofen, Milena; Beier, Christoph; Regelous, Marcel; Krumm, Stefan; Günther, Thomas (Chemical Geology, 2018)

Extreme intensity of fluid-rock interaction during extensive intraplate volcanism - Beier, Christoph; Bach, Wolfgang; Busch, Alexander V.; Genske, Felix S.; Hübscher, Christian; Krumm, Stefan (Geochimica Et Cosmochimica Acta, 2019)
The initial formation and temporal evolution of large igneous plateaus and the extent to which these large enigmatic igneous features impact on their immediate and distant ecological surrounding remains a matter of active research. The compositional variability in large igneous provinces has mainly been attributed to changes in the melting regime and shallow crustal processes and commonly ranges from depleted tholeiitic basaltic to enriched alkaline lavas. Large igneous provinces erupted in the submarine environment however, may also experience intense hydrothermal alteration during their formation resulting from an increased exchange between seawater and the erupting lavas during their eruptive history. The submarine Azores Plateau in the Central Northern Atlantic has generally been treated to represent such large igneous province formed since ∼10 Ma by widespread volcanism and the unique tectonic regime which results in large fault systems exposing the erupted lavas. Here, we present new seismic, petrological and major element, trace element and isotope geochemical data from a ∼1000 m stratigraphic section of submarine lavas exposed at the western Princessa Alice bank. The 22 samples recovered from the near-vertical rift wall provide evidence for intense water-rock exchange not observed anywhere in oceanic crust sampled to date. Fluid-immobile incompatible trace elements show that the samples formed from higher degrees of partial melting of a mantle source that is less enriched than the source that gives rise to the islands today. The extents of melting today are very small, implying a change in melting regime since initial formation of the Princessa Alice Plateau basalts that correspond to a melting anomaly in the Azores. Our observations indicate that the extreme levels of alteration may result from a combination of intensified magmatic activity during initial formation of the Azores Plateau and the tectonic regime providing pathways for the fluids. Our results impact on the interpretation of shallow level crustal magmatic processes, in which the contribution of crustal sources to the ascending melt may be different to what had previously been suggested. We propose that hydrothermal alteration during submarine igneous plateau forming events can drastically change the compositions of the igneous crust. The associated elemental and isotopic exchange between the oceanic crust and hydrosphere may substantially change the chemical fluxes between oceans and crust during the emplacement of oceanic plateaus.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Azores Plateau; Large igneous province; Ocean-crust exchange; Water-rock reactions

Formation of andesite melts and Ca-rich plagioclase in the submarine Monowai volcanic system, Kermadec arc - Kemner, Fabian; Haase, Karsten; Beier, Christoph; Krumm, Stefan; Brandl, Philipp (Geochemistry Geophysics Geosystems, 2015)
Andesites are typical rocks of island arcs and may either form by fractional crystallization processes or by mixing between a mafic and a felsic magma. Here we present new petrographic and geochemical data from lavas of the submarine Monowai volcanic system in the northern Kermadec island arc that display a continuous range in composition from basalt to andesite. Using petrology, major, trace, and volatile element data, we show that basaltic magmas mostly evolve to andesitic magmas by fractional crystallization. Our thermobarometric calculations indicate that the formation of the large caldera is related to eruption of basaltic-andesitic to andesitic magmas from a magma reservoir in the deeper crust. Small variations in trace element ratios between the caldera and the large active cone imply a homogeneous mantle source. Contrastingly, resurgent dome melts of the caldera stagnated at shallower depths are more depleted and show a stronger subduction input than the other edifices. The Monowai basaltic glasses contain less than 1 wt % HO and follow typical tholeiitic fractionation trends. High-An plagioclase crystals observed in the Monowai lavas likely reflect mixing of HO-saturated melt batches with hot and dry tholeiitic, decompression melt batches. The result is a relatively HO-poor mafic magma at Monowai implying that partial melting of the mantle wedge is only partly due to the volatile flux and that adiabatic melting may play a significant role in the formation of the parental melts of the Monowai volcanic system and possibly other arc volcanoes.
Keywords: fractional crystallization; glass; plagioclase; subduction; Tonga-Kermadec; volatiles

Geochemische und fazielle Muster in peritidalen Kalk/Dolomit-Zyklen der oberen Bellerophon-Schichten (Oberperm) in den Südalpen. - Buggisch, Werner; Krumm, Stefan; Noe, Sibylle (Abhandlungen der Geologischen Bundesanstalt Wien, 1994)
UnivIS-Import:2015-03-05:Pub.1994.nat.dgeo.IGM.LG.geoche

Geochemistry of volcanic glasses from the Louisville Seamount Trail (IODP Expedition 330): Implications for eruption environments and mantle melting - Nichols, Alexander R.L.; Beier, Christoph; Brandl, Philipp; Buchs, David M.; Krumm, Stefan (Geochemistry Geophysics Geosystems, 2014)
Volcanic glasses recovered from four guyots during drilling along the Louisville Seamount Trail, southwest Pacific, have been analyzed for major, trace, and volatile elements (HO, CO, S, and Cl), and oxygen isotopes. Compared to other oceanic island settings, they are geochemically homogeneous, providing no evidence of the tholeiitic stage that characterizes Hawai'i. The degrees and depth of partial melting remained constant over 1-3 Ma represented by the drill holes, and along-chain over several million years. The only exception is Hadar Guyot with compositions that suggest small degree preferential melting of an enriched source, possibly because it erupted on the oldest and thickest lithosphere. Incompatible element enriched glass from late-stage volcaniclastics implies lower degrees of melting as the volcanoes moved off the melting anomaly. Volcaniclastic glasses from throughout the igneous basement are degassed suggesting generation during shallow submarine eruptions (<20 mbsl) or as subaerial flows entered the sea. Drill depths may no longer reflect relative age due to postquench downslope movement. Higher volatile contents in late-stage volcaniclastics indicate submarine eruptions at 118-258 mbsl and subsidence of the edifices below sea level by the time they erupted, or generation in flank eruptions. Glass from intrusion margins suggests emplacement 100 m below the surface. The required uplift to achieve these paleo-quench depths and the subsequent subsidence to reach their current depths exceeds that expected for normal oceanic lithosphere, consistent with the Louisville melting anomaly being <100C hotter than normal asthenosphere at 50-70 Ma when the guyots were erupted. © 2014. American Geophysical Union. All Rights Reserved.
Keywords: eruption environments; intraplate melting dynamics; major and trace elements; mantle thermal anomaly; uplift and subsidence

Magmatic evidence for carbonate metasomatism in the lithospheric mantle underneath the Ohře (Eger) Rift - Brandl, Philipp; Genske, Felix; Beier, Christoph; Haase, Karsten; Sprung, Peter; Krumm, Stefan (Journal of Petrology, 2015)
Magmas erupted in intracontinental rifts typically form from melting of variable proportions of asthenospheric or lithospheric mantle sources and ascend through thick continental lithosphere. This ascent of magma is accompanied by differentiation and assimilation processes. Understanding the composition of rift-related intracontinental volcanism is important, particularly in densely populated active rift zones such as the Ohře (Eger) Rift in Central Europe. We have sampled and analysed nephelinites from Železná hůrka (Eisenbühl), the youngest (<300 ka) Quaternary volcano related to the Ohře Rift where frequent earthquake swarms indicate continuing magmatic activity in the crust. This nephelinite volcano is part of a larger eruptive centre (Mỳtina Maar) representing a single locality of recurrent volcanism in the Ohře Rift. We present a detailed petrographic, mineralogical and geochemical study (major and trace elements and Sr-Nd-Hf-O isotopes) of Železná hůrka to further resolve the magmatic history and mantle source of the erupted melt. We find evidence for a highly complex evolution of the nephelinitic melts during their ascent to the surface. Most importantly, mixing of melts derived from different sources and of strong chemical contrast controls the composition of the erupted volcanic products. These diverse parental melts originate from a highly metasomatized subcontinental lithospheric mantle (SCLM) source. We use a combined approach based on mineral, glass and whole-rock compositions to show that the mantle underneath the western Ohře Rift is metasomatized dominantly by carbonatitic melts. The nephelinites of Železná hůrka formed by interaction between a carbonatitic melt and residual mantle peridotite, partial crystallization in the lithospheric mantle and minor assimilation of upper continental crust. Thermobarometric estimates indicate that the stagnation levels of the youngest volcanism in this part of the Ohře Rift were deeper than the focal depths of recent earthquake swarms, indicating that those are not directly linked to magma ascent. Furthermore, close mineralogical and geochemical similarities between the Železná hůrka nephelinite and fresh kimberlites may point towards a genetic link between kimberlites, melilitites and nephelinites.
Keywords: Assimilation; Carbonated peridotite; Continental rift; Mantle metasomatism; Nephelinite

Magmatic evolution and source variations at the Nifonea Ridge (New Hebrides Island Arc) - Lima, Selma; Haase, Karsten; Beier, Christoph; Regelous, Marcel; Brandl, P. A.; Hauff, F.; Krumm, Stefan (Journal of Petrology, 2017)
Keywords: Back-arc melting; Mantle heterogeneity; Nb-enriched basalts; New Hebrides island arc

Metamorphic and Structural Evolution of the Southern Shackleton Range during the Ross Orogeny. - Buggisch, Werner; Kleinschmidt, Georg; Kreuzer, Hans; Krumm, Stefan (Polarforschung, 1994)
UnivIS-Import:2015-03-05:Pub.1994.nat.dgeo.IGM.LG.metamo

Origin of Silicic Magmas at Spreading Centres-an Example from the South East Rift, Manus Basin - Beier, Christoph; Bach, Wolfgang; Turner, Simon; Niedermeier, Dominik; Woodhead, Jon; Erzinger, Joerg; Krumm, Stefan (Journal of Petrology, 2015)
There has been much recent interest in the origin of silicic magmas at spreading centres away from any possible influence of continental crust. Here we present major and trace element data for 29 glasses (and 55 whole-rocks) sampled from a 40 km segment of the South East Rift in the Manus Basin that span the full compositional continuum from basalt to rhyolite (50-75 wt % SiO2). The glass data are accompanied by Sr-Nd-Pb, O and U-Th-Ra isotope data for selected samples. These overlap the ranges for published data from this part of the Manus Basin. Limited increases in Cl/K ratios with increasing SiO2, La-SiO2 and Yb-SiO2 relationships, and the oxygen isotope data rule out models in which the more silicic lavas result from partial melting of altered oceanic crust or altered oceanic gab-bros. Rather, the data form a coherent array that is suggestive of closed-system fractional crystallization and this is well simulated by MELTS models run at 0.2 GPa and QFM (quartz-fayalite-magnetite buffer) with 1 wt % H2O, using a parental magma chosen from the basaltic glasses. Although some assimilation of altered oceanic crust or gabbro cannot be completely ruled out, there is no evidence that this plays an important role in the origin of the silicic lavas. The U-series disequilibria are dominated by U-238 and Ra-226 excesses that limit the timescale of differentiation to less than a few millennia. Overall, the data point to rapid evolution in relatively small magma lenses located near the base of thick oceanic crust; we speculate that this was coupled with relatively low rates of basaltic recharge. A similar model may be applicable to the generation of silicic magmas elsewhere in the ocean basins.
Keywords: silicic lavas; differentiation; oceanic spreading centre; South East Rift; Manus Basin

Oxygen isotope and trace element compositions of platiniferous dunite pipes of the Bushveld Complex, South Africa - Signals from a recycled mantle component? - Günther, Thomas; Haase, Karsten; Junge, Malte; Oberthür, Thomas; Wölki, Dominic; Krumm, Stefan (Lithos, 2018)
Platiniferous dunite pipes occur in the lower mafic/ultramafic portion of the Rustenburg layered Suite of the Bushveld large igneous province (LIP). Olivine compositions in these pipes range from forsterite (Fo) 80 to 35 mol% and suggest crystallization from variably evolved magmas at high temperatures (similar to 1200 degrees C). The most primitive olivines are from a stock unit and have the highest contents of Ni (>0.15 wt%) and lowest contents of Mn (<0.3 wt%). Fractional crystallization and partial melting of pyroxenite host rock play a significant role in the formation of the fayalitic olivines with its high Mn contents (>0.3 wt%). High delta O-18 values of olivine (5.7-7.0 parts per thousand) and pyroxene (6.7-7.4 parts per thousand) are akin to those of the Lower and Critical Zone of the Bushveld intrusion suggesting a common origin. The constant high O isotope ratios with variable Fo contents in the olivines are unlike trends observed in olivine phenocrysts in magmas forming by assimilation-fractional crystallization. We suggest that the high delta O-18 in the most primitive dunites reflect that of the primary melt of the Bushveld pipes, indicating either a bulk assimilation of crust prior to pipe formation or a contribution from recycled oceanic crust in the subcontinental lithospheric mantle (SCLM). The latter scenario is supported by the high Ni/Mn ratios in primitive pipe olivine that might be inherited from melting of a pyroxene-rich mantle source. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Bushveld Complex; Kaapyaal Craton; Large Igneous Province; Olivine; Trace elements; Oxygen isotopes

Oxygen isotope and trace element compositions of platiniferous dunite pipes of the Bushveld Complex, South Africa – Signals from a recycled mantle component? - Günther, Thomas; Haase, Karsten; Junge, Malte; Oberthür, Thomas; Wölki, Dominic; Krumm, Stefan (Lithos, 2018)

Oxygen isotope evidence for the formation of andesitic-dacitic magmas from the fast-spreading Pacific-Antarctic Rise by assimilation-fractional crystallisation - Freund, Sarah; Beier, Christoph; Krumm, Stefan; Haase, Karsten (Chemical Geology, 2013)
Andesitic to dacitic lavas occur along a 300km long portion of the Pacific-Antarctic Rise close to the intersection of the spreading axis with the Foundation seamount chain. The fresh silicic glasses have low δO isotope values between 5.6‰ and 5.1‰ whereas basaltic glasses from the same ridge section have normal MORB δO values. Additionally, two FeTi basaltic and all silicic glasses have high Cl (up to 1.1wt.%) and KO (up to 1.6wt.%) contents, indicating assimilation of hydrothermally altered material. Modelling suggests that the fractionating magma assimilated up to 30% of hydrothermally altered material after 57% fractional crystallisation of the basaltic magma in a melt lens at less than 2km depth. In contrast, the basaltic glasses show little assimilation and clinopyroxene-melt barometry indicates crystal fractionation in deeper melt sills. Relatively low HO/Ce and Li/Ce ratios as well as the low δO values and high Cl and K concentrations in the silicic glasses suggest assimilation of altered crustal rock rather than a brine. While some of the variability in highly incompatible element ratios is best explained by crystal fractionation processes of FeTi-oxides (e.g., decreasing Nb/U) others require a reaction of the melt with residual amphibole and clinopyroxene (Cl/K, Tb/Yb, Hf/Sm, Ce/Yb). The initial onset of FeTi oxide crystallisation is associated with a reduced oxygen fugacity causing sulphide saturation and significant loss of S, Cu, and Co from the evolved melts. This change to more reducing melts as a result of oxide crystallisation is supported by the strong development of a negative Eu anomaly in the andesites and dacites indicating stronger partitioning of Eu into plagioclase. Reverse mineral zoning in the evolved lavas also indicates that replenishment by mafic melts occurs in the shallow melt lens. © 2013 Elsevier B.V.
Keywords: Assimilation-fractional crystallisation; FeTi basalt; Magma evolution; Mid-ocean ridge; Oxygen isotopes; Silica-rich lava

Oxygen isotope evidence for the formation of silicic Kermadec island arc and Havre-Lau backarc magmas by fractional crystallization. - Haase, Karsten; Krumm, Stefan; Regelous, Marcel; Joachimski, Michael (Earth and Planetary Science Letters, 2011)
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LG.oxygen

Oxygen isotopes in the Azores islands: Crustal assimilation recorded in olivine - Genske, Felix; Beier, Christoph; Haase, Karsten; Turner, Simon P.; Krumm, Stefan; Brandl, Philipp (Geology, 2013)
Oxygen isotope ratios of olivine have become a widely used tool for the study of magmatic systems, especially in the interpretation of source heterogeneities in mantle plume-derived ocean island basalts. The underlying assumption is that fresh minerals provide a better guide to magma δO than bulk rock analyses and that olivine is also likely to be a major phenocryst phase in primitive magmas. However, distinctions between source compositions and the effects of subsequent magma evolution have not always been thoroughly scrutinized. For the Azores samples investigated here, we can demonstrate that the δO variation (+4.84‰ to +5.25‰ Vienna standard mean ocean water) observed in the olivine phenocryst population is closely linked to evolution in the host magmas during ascent to the surface. We observe a linear, positive correlation between forsterite (Fo) content and δO in all of the individual island lava suites. This forces us to conclude that the low oxygen isotope ratios result from combined assimilation and fractional crystallization processes, the assimilant being hydrothermally (temperature > 250 C) altered, lower oceanic crust. Linear regression of the measured δO olivine values to Fo suggests a homogeneous mantle source with δO = +5.2‰ ± 0.1‰. © 2013 Geological Society of America.

Palaeoclimate reconstructions of the Middle Jurassic of Kachchh (western India): An integrated approach based on palaeoecological, oxygen isotopic, and clay mineralogical data - Fürsich, Franz; Singh, Indabir; Joachimski, Michael; Krumm, Stefan; Schlirf, M; Schlirf, S. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2005)
The Middle Jurassic sedimentary succession of the Kachchh Basin shows significant changes in lithology, faunal content and diversity across the Bathonian-Callovian boundary. The change in lithology from predominantly carbonates in the Middle and Late Bathonian to siliciclastics in the Callovian is accompanied by a drop in species diversity from high to moderate. Characteristic faunal elements of the Bathonian (corals, sponges, the bivalves Eligmus and members of the Opinae) are absent or rare in the Callovian. In contrast, Callovian sediments contain comparatively high proportions of nuculid bivalves. The clay mineral assemblage reveals prominent variations in the smectite vs. kaolinite abundance, especially during the Bathonian to Callovian transition. From the Bajocian to the Middle Bathonian, smectite becomes the dominant clay mineral and is nearly exclusively present in the Late Bathonian. Towards the Middle Callovian, its content gradually decreases and kaolinite becomes the dominant clay mineral. Illite generally is only a minor component throughout the Middle Jurassic. Based on these results, the Bajocian to Middle Bathonian time interval is interpreted to represent subtropical climatic conditions with seasonal droughts and a moderate supply of terrigenous clastics to the basin. The Late Bathonian was a period with a semi-arid climate, hot seasonal droughts and a minor input of terrigenous clastics. The increase in kaolinite contents in the Callovian suggests a subtropical humid climate with less prominent seasonal droughts and a higher input of siliclastics into the basin accompanied by a higher nutrient influx. Oxygen isotope ratios measured on Bathonian to early Callovian brachiopod shells give palaeotemperatures of 19-24°C. Callovian to Oxfordian paleotemperatures calculated from oxygen isotopes measured on belemnite rostra range from 11 to 21°C. The lower palaeotemperatures estimated from the oxygen isotopic composition of belemnite calcite are explained by assuming that the belemnites spent most of their life span in colder regions of the Malagassy Gulf and migrated into the warmer subtropical waters of the Kachchh Basin. Combining these various lines of evidence, the changes in lithology and faunal composition taking place in the Kachchh Basin during the Middle Jurassic appear to reflect largely a change towards increasing humidity rather than a distinct decrease in water temperature. © 2004 Elsevier B.V. All rights reserved.
Keywords: Clay mineralogy; India; Jurassic; Kachchh Basin; Oxygen isotopes; Palaeoclimate; Palaeoecology

Paleozoic cold seep carbonates from Europe and North Africa - an integrated isotopic and geochemical approach. - Buggisch, Werner; Krumm, Stefan (Facies, 2005)
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.LG.paleoz

Phasenanalyse und Spurenelementgehalte von Riffsanden der Seychellen - Bausch, Walter; Krumm, Stefan; Munnecke, Axel (Erlanger Beiträge zur Petrographischen Mineralogie, 2012)
Riffsande der Seychellen-Inseln setzen sich im Mittel aus knapp 60 % Aragonit und knapp 30 % Mg-Calcit zusammen. Quarz und zwei andere Calcit-Varietäten stellen den Rest. Häufigstes Spurenelement ist Magnesium mit 1,6 %, gefolgt von Strontium mit 4550 ppm (Mittelwerte; bei erheblicher Streubreite). Extrapoliert auf reine Komponenten, finden sich 6-7 % Mg im Mg-Calcit, sowie 7160 ppm Sr im Aragonit. Eine Gleichung der negativen Korrelation Sr/Mg kann festgelegt werden. Die Riffsande variieren auch in den Korngrößen. Grobe Sande enthalten relativ mehr Mg-Calcit, feine Sande relativ mehr Aragonit. Konsequenterweise variieren auch die Spurenelementgehalte sinngemäß: feine Sande führen relativ mehr Sr, grobe Sande relativ mehr Mg.
Keywords: Calcit; Riffsande; Seychellen; Aragonit; Mg-Calcit; Strontium; Sr; Spurenelemente

Primitive andesites from the Taupo Volcanic Zone formed by magma mixing - Beier, Christoph; Haase, Karsten; Brandl, Philipp; Krumm, Stefan (Contributions To Mineralogy and Petrology, 2017)
Andesites with Mg# >45 erupted at subduction zones form either by partial melting of metasomatized mantle or by mixing and assimilation processes during melt ascent. Primitive whole rock basaltic andesites from the Pukeonake vent in the Tongariro Volcanic Centre in New Zealand’s Taupo Volcanic Zone contain olivine, clino- and orthopyroxene, and plagioclase xeno- and antecrysts in a partly glassy matrix. Glass pools interstitial between minerals and glass inclusions in clinopyroxene, orthopyroxene and plagioclase as well as matrix glasses are rhyolitic to dacitic indicating that the melts were more evolved than their andesitic bulk host rock analyses indicate. Olivine xenocrysts have high Fo contents up to 94%, δO of +5.1‰, and contain Cr-spinel inclusions, all of which imply an origin in equilibrium with primitive mantle-derived melts. Mineral zoning in olivine, clinopyroxene and plagioclase suggest that fractional crystallization occurred. Elevated O isotope ratios in clinopyroxene and glass indicate that the lavas assimilated sedimentary rocks during stagnation in the crust. Thus, the Pukeonake andesites formed by a combination of fractional crystallization, assimilation of crustal rocks, and mixing of dacite liquid with mantle-derived minerals in a complex crustal magma system. The disequilibrium textures and O isotope compositions of the minerals indicate mixing processes on timescales of less than a year prior to eruption. Similar processes may occur in other subduction zones and require careful study of the lavas to determine the origin of andesite magmas in arc volcanoes situated on continental crust.
Keywords: Crustal magmatic processes; Magma mixing; Primitive andesites; Subduction zones; Taupo Volcanic Zone

Reply to discussion by RN Scoon and AA Mitchell on 'Oxygen isotope and trace element compositions of platiniferous dunite pipes of the Bushveld Complex, South Africa - Signals from a recycled mantle component?' - Günther, Thomas; Haase, Karsten; Junge, Malte; Oberthuer, Thomas; Wölki, Dominic; Krumm, Stefan (Lithos, 2019)
CRIS-Team WoS Importer:2019-02-22

Sample preparation effects on illite "crystallinity" measurement; gradation and particle orientation. - Krumm, Stefan; Buggisch, Werner (Journal of Metamorphic Geology, 1991)
Specimen thickness is the main experimental factor controlling the results of illite crystallinity (IC) or crystallite size measurements on sedimentation slides. Orientation effects control the measured peak intensity. A plateau with constant peak breadths is observed if thin slides of well ordered, platy illites are used. A similar plateau can be recognized for thick preparations of specimens from less ordered materials, but not from well ordered ones. Therefore, it is suggested that IC is determined on very thin sedimentation slides with a thickness of 0.25 mg/cm2 or less. -from Authors
UnivIS-Import:2015-03-05:Pub.1991.nat.dgeo.IGM.LG.sample

Sedimentology, geochemistry and tectonic setting of the Neoproterozoic Malmesbury Group (Tygerberg Terrane) and its relation to neighbouring terranes, Saldania Fold Belt, South Africa - Buggisch, Werner; Kleinschmidt, Georg; Krumm, Stefan (Neues Jahrbuch für Geologie und Paläontologie-Abhandlungen, 2010)
The metamorphic grade and the facies of the Neoproterozoic Malmesbury Group of the Saldania Fold Belt changes abruptly across major fault zones. Therefore three different tectonostratigraphic domains were assumed: The Tygerberg Terrane, the Swartland Terrane and the Boland Terrane. Additionally, a small block with volcanic greenstones and carbonates (Bridgetown Formation) is squeezed between the Swartland and Boland terranes. Based on the investigations of sedimentray and tectonic structures, geochemistry and data from literature, a geodynamic model of the Saldania Belt is proposed including: (1) An ocean between South America with the attached Tygerberg Terrane and the Swartland Terrane, (2) rifting between the Swartland Terrane and South Africa with the attached Boland Terrane, subduction ot the ocean (1) towards west, followed by subduction of the ocean (2) underneath the Swartland Terrane. © 2010 Schweizerbart'sche Verlagsbuchhandlung, Stuttgart, Germany.
Keywords: Malmesbury; Neoproterozoic; Saldania fold belt; Sedimentology structure; South africa

Stratigraphy, metamorphism and nappe‑tectonics in the Shackleton Range (Antarctica). - Buggisch, Werner; Kleinschmidt, Georg; Kreuzer, Hans; Krumm, Stefan (Geodätische und geophysikalische Veröffentlichungen. Reihe I, 1990)
UnivIS-Import:2015-03-05:Pub.1990.nat.dgeo.IGM.LG.strati

Systematic variations of trace element and sulfur isotope compositions in pyrite with stratigraphic depth in the Skouriotissa volcanic-hosted massive sulfide deposit, Troodos ophiolite, Cyprus - Keith, Manuel; Haase, Karsten; Klemd, Reiner; Krumm, Stefan; Strauss, Harald (Chemical Geology, 2016)

The age of the Early Palaeozoic deformation and metamorphism in the Argentine Precordillera - evidence from K/Ar-data - Buggisch, Werner; von Gosen, Werner; Henjes-Kunst, Friedhelm; Krumm, Stefan (Zentralblatt für Geologie und Paläontologie, Teil I, Geologie, 1994)
UnivIS-Import:2015-03-05:Pub.1994.nat.dgeo.IGM.LG.theage

The magmatic evolution of young island arc crust observed in gabbroic to tonalitic xenoliths from Raoul Island, Kermadec Island Arc - Haase, Karsten; Lima, Selma; Krumm, Stefan; Garbe-Schönberg, Dieter (Lithos, 2014)
We provide new geochemical and O isotope data for minerals and whole rocks of a suite of gabbroic to tonalitic xenoliths from Raoul Island in the Kermadec island arc. The plagioclase, olivine and clinopyroxene compositions are similar to those observed in the Raoul Island lavas supporting a close relationship of the plutonic and volcanic rocks by crystal fractionation. Plagioclase in gabbros is significantly more An-rich than in similar rocks from oceanic spreading axes reflecting higher water contents in the island arc magmas. Incompatible element and O isotope data suggest that the gabbroic rocks formed from accumulation of minerals of the ascending magmas whereas the tonalites represent highly evolved magmas after extreme fractional crystallization. Temperatures of the magmas calculated from O isotope equilibria and pyroxene thermometers range from about 1200. °C in the mafic to 800. °C in felsic rocks. Barometry of the rocks suggests that gabbros formed between 12 and 18. km depth and tonalites shallower which is in agreement with seismic models of island arc crustal layering. The xenolith data from Raoul Island support seismic studies indicating that some portions of the Tonga-Kermadec island arc show similar layering of felsic and mafic rocks to the Izu-Bonin and the fossil Talkeetna island arcs.
Keywords: Crust formation; Fractional crystallization; Magma differentiation; O isotopes

The sedimentary and structural evolution of the Argentine Precordillera - the key of the history of an exotic terrane. - Buggisch, Werner; Bordonaro, Oswaldo; Cañas, Fernando; von Gosen, Werner; Keller, Martin; Krumm, Stefan; Lehnert, Oliver; Loske, Werner (Zeitschrift für Angewandte Geologie, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dgeo.IGM.LG.thesed_2

Upper crustal fluids in a large fault system: microstructural, trace element and oxygen isotope study on multi-phase vein quartz at the Bavarian Pfahl, SE Germany - Schaarschmidt, Anna; Haase, Karsten; de Wall, Helga; Bestmann, Michel; Krumm, Stefan; Regelous, Marcel (International Journal of Earth Sciences, 2018)
Fault systems are zones of crustal weakness and are used as pathways for ascending hydrothermal fluids. One impressive example is the more than 150 km long Bavarian Pfahl system at the SW boundary of the Bohemian Massif. Dextral ductile shearing of Moldanubian basement has shaped a several hundred meter wide zone of mylonites and ultramylonites. This setting was reactivated under brittle conditions and infiltrated by fluids resulting in a multi-phase quartz lode. Structural analysis using scanning electron microscopy cathodoluminescence (SEM–CL) images has been carried out in combination with trace element and oxygen isotope analysis on quartz along the system. Three successive quartz phases have been distinguished due to their structural details and trace element contents. Cryptocrystalline quartz fabric in the first quartz phase results from crystallization from a silica gel, whereas in phases II and III, quartz precipitation is characterized by repeated fragmentation and sealing, visible due to strongly varying CL intensities. The δ18O of Bavarian Pfahl quartz decreases from 13.8‰ in the NW to 8.5‰ in the SE, whereas quartz from the close-by-situated Wölsendorf fluorite deposit shows δ18O between 15.9 and 18.5‰ (vs. SMOW). Flat shale-normalized rare earth element patterns point towards an upper crustal origin of the hydrothermal fluids. The southeastern part of the Bavarian Pfahl is interpreted to represent a deeper crustal level with higher mineralization temperatures (about 350 °C) compared to the rest of the Pfahl (< 250 °C
Keywords: Quartz microfabric; Cathodoluminescence; Hydrothermal fluid; Trace elements; Oxygen isotopes